Hemilaminectomy for the removal of the spinal tumors: An analysis of 901 patients - Liao, Dengyong; Li, Dan; Wang, Ruoran; Xu, Jianguo; Chen, Haifeng (Frontiers in Neurology, 2023)
Abstract Objective: We report our experience with the use of hemilaminectomy approach for the removal of benign intraspinal tumors. Method: A retrospective review of 1067 patients who underwent hemilaminectomy in our hospital between 2013 and 2019 was analyzed. Baseline medical data were collected. 116 patients were excluded due to degenerative diseases, spinal bone tumors, and malignant tumors. The remaining 901 patients (916 tumors) were enrolled. The Dennis Pain Scale (DPS) was used to assess improvement in pain before surgery and during long-term follow-up. Neurological status was assessed using the American Spinal Injury Association (ASIA) impairment scale. Results: The age of the patients was 48.7 ± 15.3 years, the duration of symptoms was 16.5 ± 32.0 months, and the tumor size was 2.6 ± 1.4 cm. 302 tumors were located in the cervical region, 42 in the cervicothoracic region, 234 in the thoracic region, 57 in the thoracolumbar region, and 281 in the lumbar and lumbosacral region. Twenty-three tumors were ventrally located, 677 were dorsal or dorsolateral, 63 were intramedullary, 87 were epidural, and the rest were dumbbell-shaped. The most common pathologies were schwannomas (601, 66.7%) and meningiomas (172, 19.1%). Total excision was achieved at 97.8%. The operative time was 94.3 ± 32.6 min and the blood loss during surgery was 96. 9 ± 116.5 ml. The symptom of pain improved in 87.0% of patients during long-term follow-up, neurological function improved in 68.3% and remained unchanged at 30.5%. Conclusion: The hemilaminectomy approach was a rapid and safe procedure to remove intradural and extradural tumors. This approach has offered several advantages. It could be used for the resection of most extradural or intradural extramedullary lesions, even some intramedullary tumors.